The Effect of Dexmedetomidine, Magnesium Sulfate or Midazolam as Adjuvant to Bupivacaine in Ultrasound Guided Supraclavicular Brachial Plexus Block (Cuestiones de Fisioterapia, 2024)
Abstract: Background: Different adjuvant have been used to improve the quality of regional anesthesia. The aim of the study: It is evaluation and comparing the effects of dexmedetomidine, magnesium sulfate and midazolam when added as adjuvant to bupivacaine on the quality of US-guided supraclavicular brachial plexus block. Patients and methods: This prospective, randomized controlled trial was conducted on 100 patients undergoing upper limb surgery under US-guided supraclavicular brachial plexus block. These patients were randomized into 4 equal groups. 15 ml of 0.5% bupivacaine plus each of 5ml normal saline, 1µg/kg dexmedetomidine, 3 mg/kg of 10% magnesium sulfate and 50µg/kg of midazolam were used in the control (B/S) group, dexmedetomidine (B/D) group, magnesium sulfate (B/MgS) group and midazolam (B/M) group, respectively. Onset and duration of sensory and motor blocks, time to first analgesic request, total postoperative analgesic consumption, hemodynamic changes, and the associated side effects were recorded. Results: The block onset times, intraoperative analgesic potency, duration of postoperative analgesia and rates of the associated side effects in B/D, B/MgS, and B/M groups were significantly better than in B/S (Control) group (P <0.001) and in B/D group they were significantly better than in B/MgS and B/M groups (P =0.042) and in B/MgS group they were significantly better than that in B/M group. Conclusion: Addition of Dexmedetomidine, Magnesium sulfate and midazolam as adjuvant to bupivacaine are efficient in improving the characteristics of supraclavicular brachial plexus block but Dexmedetomidine is the most efficient one that followed by Magnesium sulfate and then by midazolam.